Gaya Hidup Mahasiswi Pengguna Riasan Wajah - Cucum Alfi Mawarni; Yuhastina Yuhastina; Abdul Rahman (Journal of Education on Social Science (JESS), 2021)
The focus of the study was the lifestyle of female students who used makeup, particularly those who used it every day. This study is a descriptive qualitative study, while the sampling technique used is purposive sampling technique with all six informants who are FKIP UNS students and active users of makeup. Then, for data collection techniques that are done by way of interviews and observations. Meanwhile, the purpose of the study was to find out the lifestyle displayed by female students who use makeup. The results of this study include their efforts in meeting their cosmetic needs, the way they shop for cosmetics, as well as then consumptive behaviors that are then displayed in some good habits in the use of time to priority in choosing products. Generally, these students are of the view that makeup is a thing that must be fulfilled. By using cosmetics, they feel they can appear more free and confident